The Impact of Perceived Financial Literacy and Parental Norm towards Money Management of Bidikmisi Student - Rinita Pappang; Njo Anastasia (Master of Management, School of Business and Management, Petra Christian University, 2019)
This research examines the impact of perceived financial literacy and parental norms on money management. I collected the data by spreading online and printed questionnaires towards 100 respondents of students who got Bidikmisi scholarship from several universities in Indonesia. Then, the data was processed by SmartPLS. The result of the research shows that perceived financial literacy and parental norms significantly influence money management of students who got Bidikmisi scholarship. So, the role of parents in terms of educating the children about finance shapes the knowledge of the students to manage the scholarship to fulfill the needs of the college.